Systematic Literature Review : Enhancement Interest and Readiness Entrepreneurship Student Through Entrepreneurship Education - Deni Alimaningtyas; Mohammad Syukri Ghozali; Dika Adininggar; Hanis Bachrodin (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Implementation Program Teaching Entrepreneurship help student become more creative, innovative and entrepreneurial. This is one of the solution For problem serious unemployment in Indonesia is necessary overcome. This in accordance with set goalsin Regulation President Number 6 of 2009 concerning development economy creative. Although Thus, various factor cause student No interested or Ready For entrepreneurship. Therefore that's the goal from study This is For know How studying entrepreneurship influence interest and readiness student For entrepreneurship.Method review literature systematic (SLR) is used in study This . The result show that education entrepreneurship give significant and positive impact to students , incl interest , readiness , spirit , and motivation For entrepreneurship .